An analytical method for the desorption superposition effect in commingled production of coalbed methane and its application: A case study of the Xiaotun mine field in western Guizhou Province, China - Chen GUO; Yan JI; Chenyi ZHAO; Lingling LU; Xinhang YU; Junzhe GAO; Houqiang LI; Xuyang ZHANG; Xiang WANG; Hongbin HE; Runhan ZHANG (Meitian dizhi yu kantan)
ObjectiveThe commingled production of coalbed methane (CBM) serves as a significant means to increase single-well production. However, production practices reveal that the commingled production of CBM exhibits complex and varied effects and controlling factors, facing technical challenges of identifying gas-producing contributions, predicting gas-producing potential, and optimizing pay interval combinations. The superposition of desorption for gas production among different coal seams determines whether high CBM production can be achieved using commingled production. MethodsThis study proposed an analytical method for the desorption superposition effect in the commingled production of CBM, involving determining desorption sequences, analyzing the superposition of desorption intervals and the matching of desorption stages, and predicting well-controlled desorption capacities. The proposed method was applied to the Xiaotun mine field in western Guizhou Province, China. Results and conclusionsThe results indicate that coal reservoirs in the Xiaotun mine field feature high adsorption capacities, low gas saturation, and low critical desorption pressures. The CBM pay intervals can be categorized into the upper and lower desorption systems. The upper desorption system manifested a desorption sequence of the No.6 upper, No.7, No.6 middle, and No.6 lower coal seams, while the lower desorption system displayed a desorption sequence of the No.34 and No.33 coal seams. Using changes in the working fluid during the production process as an indicator, this study analyzed the desorption processes of coal seams during the commingled production of CBM. The analytical results reveal that the synchronous desorption of the No.6 upper, No.7, No.6 middle, and No.6 lower coal seams can be achieved within a working fluid of 45 m and the synchronous desorption of the No.33 and No.34 coal seams can be gained within a working fluid of 92 m. Isothermal adsorption curves discovered the matching of the coal seams' desorption stages. The low critical desorption pressures allowed various coal seams to directly enter the sensitive desorption stage after desorption, suggesting high desorption efficiency and effective matching. This creates favorable conditions for high CBM production. However, limitations like insufficient pressure drop space and long drainage periods impose high requirements for coal seam stimulation and CBM production. The well-controlled desorption capacities and their time-varying curves indicate that gas desorption capacities peaked in the case of the synchronous desorption of all pay intervals within the respective desorption systems. In this case, the upper and the lower desorption systems yielded well-controlled desorption capacities of 378.09×104 m3 (daily average: 4.20×104 m3) and 199.11×104 m3 (daily average: 1.08×104 m3), respectively. Both desorption systems demonstrated satisfactory desorption superposition effect, each forming a favorable pay interval combination for the commingled production of CBM. The proposed method will provide a reference for identifying gas-producing contributions, predicting gas-producing potential, and optimizing pay interval combinations for the commingled production of CBM.